The Effect of Electrode Angle in Forward Welding Thechnique On Fusion Depth - Hafni Hafni; Rifqi Rifqi (Jurnal Teknik Mesin, 2019)
Shielded metal arc welding (SMAW) or manual metal arc welding (MMAW) is included in a group of fusion welding that uses heat generated by a jump in electric ions that occur between the cathode and anode (the tip of the electrode and the surface of the base metal), thus melting together. During the melting process between the electrode and the base metal is protected by a protective gas that comes from the flux of electrodes which fuses during the welding process, then in the process of freezing the flux floats above the weld metal turns into slag, this slag serves to hold the cooling rate on the metal weld. Penetration (fusion depth) of weld metal on base metal is greatly influenced by heat input. This heat input is also influenced by the welding technique and the electrode angle. In this research, advanced welding techniques are used, namely smelting occurs in front of the electrode and the electrode angle is 70°, 75°, 80o, 85o and 90°. the base metal used is low carbon steel ST 37, the electrode used is the AWS E 6013 electrode with a diameter of 3.2 mm with a current of 85 amperes, a voltage of 30 volts. Welding speed 2.49 mm /s. From the results of a macro photo, it can be seen that the electrode angle greatly affects the width and depth of penetration, where at the angle of the 900 electrode it has penetration: 88 µm wide and 6.6 µm depth.